Complete recovery of severe coronavirus disease 2019 (COVID-19) infection in an obese patient - Susanti, Vina Yanti; Anggraeni, Vita Yanti; Akbar, Adrianus; Leo, Benedreky (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
There is strong evidence indicating that excess adiposity in obesity impacts immune function and host defence. However, almost no known mechanism of how the immune and host defence are affected by the low-grade inflammatory response of the obese has been established. The significance of altered immune response in obesity was presumed to be an independent risk factor for increased morbidity and mortality following the influenza pandemic back in 2009. Similarly, obesity is linked with a higher risk of severity and a worse clinical outcome of severe acute respiratory coronavirus 2 (SARS-COV-2) infection.This case reports a complete recovery of a severe coronavirus disease 2019 (COVID-19) infection despite having morbid obesity aggravated by metabolic syndrome.